ANALISIS YURIDIS MENGENAI KEDUDUKAN ANAK TERHADAP HARTA BERSAMA ORANGTUANYA YANG BERCERAI MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 (STUDI KASUS PUTUSAN NO.406/PDT/2018/PT.MKS): The Position Of Children Concerning Property With Their Divorce Parents According To Marriage Law (Case Study Ruling No.406/Pdt/2018/Pt.Mks) - Nurliyarti, Nabila; Muriani (Faculty of Law, Universitas Trisakti, 2024)
A marriage that takes place without a prior marriage agreement will give rise to joint property. Joint Property is property acquired by a husband and wife during the marriage, except for gifts or inheritance.In the event of a breakdown in marital relations, joint assets will be divided equally between husband and wife. The main issue is whether it is possible for children in a marriage to get property with their divorced parents according to the Marriage Law, as well as the factors the judge considers in giving a share of the joint property of divorced parents to children, whether it is in accordance with the regulations per Law. Invitation. To answer the main problem, the author conducted normative juridical research with descriptive research characteristics using secondary data which was processed qualitatively and then to draw conclusions using a deductive method. Based on research results and discussion analysis, it shows that the possibility of children receiving a share of joint assets from theirdivorced parents is not explicitly regulated in the marriage law. as well as the factors considered by the judge in determining whether children will receive a share of the joint assets of their divorced parents using elements of justice and to protect the welfare of children in marriage.